Disturbed soil properties and geotechnical design - Schofield, A. N. (Andrew Noel), 1930- (Thomas Telford, 2005)
This is an easily accessible account of critical state of soil mechanics, geotechnical centrifuge testing and the original Cam-Clay model invented by the author.